Growth of Endophytic Bacteria from Klutuk Banana Plant (Musa balbisiana Colla) with Inoculation Trial on Rice Plants (Oryza sativa) - Anggun Dwi Nur Annisa; Triastuti Rahayu; Yasir Sidiq (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2024)
Four potential bacteria have been isolated from Klutuk banana plant. They exhibited IAA production. Since the bacterial inoculation to plant should be performed in exponential phase of bacterial growth, information of the growth is crucial. This study aimed to analyze the growth rate of eight isolates and examine the effect of bacterial inoculation by initial trial on rice plants. For this purpose, four endophytic bacteria from Klutuk banana were cultured and examined using 600nm spectrophotometer. The growth of the isolates was calculated every two hours for 16 hours bacterial growth in the nutrient broth medium. The inoculation trial of bacteria to rice plants was conducted with three replicates. This inoculation was begun by germinating the rice seed and the radicle was observed. Then, the germinated rice seedlings were soaked in the bacterial suspension for 5 minutes in room temperature. The results showed that the exponential phase of all isolates was observed 6 hours after shaking. Inoculation using 6-hour-incubated K7 isolate significantly improved the length of root of rice plants. Additionally, this isolate improved the number of root and shoot length without significant difference. Thus, these results provide important information of the growth phase and inoculation effect new isolated endophytic and rhizosphere bacteria.